Orthology-Based Estimate of the Contribution of Horizontal Gene Transfer from Distantly Related Bacteria to the Intraspecific Diversity and Differentiation of Xylella fastidiosa - Giuseppe Firrao; Marco Scortichini; Laura Pagliari (Pathogens, 2021)
Xylella fastidiosa is a xylem-limited bacterium phylogenetically related to the xanthomonads, with an unusually large and diversified range of plant hosts. To ascertain the origin of its peculiarities, its pan-genome was scanned to identify the genes that are not coherent with its phylogenetic position within the order Xanthomonadales. The results of the analysis revealed that a large fraction of the genes of the Xylella pan-genome have no ortholog or close paralog in the order Xanthomonadales. For a significant part of the genes, the closest homologue was found in bacteria belonging to distantly related taxonomic groups, most frequently in the Betaproteobacteria. Other species, such as Xanthomonas vasicola and Xanthomonas albilineans which were investigated for comparison, did not show a similar genetic contribution from distant branches of the prokaryotic tree of life. This finding indicates that the process of acquisition of DNA from the environment is still a relevant component of Xylella fastidiosa evolution. Although the ability of Xylella fastidiosa strains to recombine among themselves is well known, the results of the pan-genome analyses stressed the additional relevance of environmental DNA in shaping their genomes, with potential consequences on their phytopathological features.